Association between the C-reactive protein-albumin-lymphocyte index and all-cause mortality in Chinese older adults: a national cohort study based on CLHLS from 2014 to 2018 - Hu, Tian; Wang, Taotao; Luo, Xiaojing; Hu, Zheng (Frontiers in Nutrition, 2025)
BackgroundThe C-reactive protein-albumin-lymphocyte (CALLY) index, a novel inflammation-immune-nutritional biomarker, has not been comprehensively evaluated for mortality risk prediction in older populations. Here, we investigate the relationship between the CALLY index and all-cause mortality in Chinese adults aged ≥ 60 years.MethodsData were obtained from the 2014 to 2018 wave of the Chinese Longitudinal Healthy Longevity Survey (CLHLS). Upon applying a natural logarithmic transformation to the CALLY index, the lnCALLY was stratified into tertiles. Kaplan-Meier analysis and the log-rank test were employed to assess the cumulative survival probability across lnCALLY-stratified older adults populations. Cox proportional hazards regression was utilized to investigate the association between lnCALLY and all-cause mortality. Receiver operating characteristic (ROC) curves and area under the curve (AUC) values were conducted to evaluate the predictive capacity of lnCALLY for all-cause mortality. Restricted cubic splines (RCS) with four knots were applied to explore the potential non-linear dose-response association of lnCALLY with all-cause mortality. Subgroup analyses and sensitivity analyses were conducted to ensure validity.ResultsA total of 1,738 older adults participants were included in this cohort. Over a median follow-up of 3.3 years, 580 deaths (33.3%) occurred. The multivariable Cox regression demonstrated that the highest lnCALLY tertile was associated with a 40% reduced mortality risk compared to the lowest tertile [adjusted hazard ratio (HR) = 0.60, 95% confidence interval (CI): 0.49–0.73]. Kaplan-Meier curves revealed significantly higher survival probabilities in individuals with elevated lnCALLY (P < 0.001). Time-dependent ROC analysis showed that the AUC of lnCALLY for predicting all-cause mortality at 1-, 2-, and 3-year were 0.751, 0.746, and 0.762, respectively. RCS demonstrated an approximate “L”-shaped negative correlation between lnCALLY and all-cause mortality (Poverall < 0.001, Pnon–linearity = 0.364). Subgroup and sensitivity analyses confirmed robustness, with no significant interactions observed across demographic or clinical strata.ConclusionThese findings suggest that the CALLY index serves as a practical prognostic biomarker for monitoring survival in older populations, underscoring the interplay of inflammation, immunity, and nutrition in aging-related mortality.